The idea of Rome in Late Antiquity from eternal city to imagined utopia - Papadopoulos, Yannis 1960- (Amsterdam University Press, 2021)
Cover -- Table of Contents -- Introduction: Between a Physical and an Imaginary City -- I. Looking Backwards: Ordo Renascendi -- II. The Adventus of Constantius -- III. Between Rome and Athens -- The Artificial Romanitas of Julian -- IV. Between the Altar and the Court -- Symmachus and Claudian in Action -- V. Between Christ and a Roman Place -- The Emergence of Christian Rome in Time and Space -- VI. Between Jerusalem and Babylon -- The Archetype of Rome in the City of God -- Conclusions: From Rome to Eternity -- Bibliography -- Index
Keywords: Spätantike; Romidee